Environmental Uncertainty sebagai Pemoderasi Budaya Organisasi, Sistem Informasi, Narcissm Behavioral, Sistem Pengendalian Intern, dan Fraudulent Financial Reporting - Pituringsih, Endar; Basuki, Prayitno; Akram, Akram (E-Jurnal Akuntansi, 2023)
The aim of this research is to analyze the influence of organizational culture, artificial intelligence-based accounting information systems, and narcissistic behavior on internal control systems that are moderated by environmental uncertainty. The research also tested the influence of the internal control system on fraudulent financial reporting. This research was conducted at a hotel on Lombok Island. The total research population was 73 hotels with 146 research respondents. The data analysis method uses Moderate Regression Analysis (MRA). The research results show that organizational culture and artificial intelligence-based accounting information systems have a positive effect on the internal control system. However, narcissistic behavior has no influence on the internal control system. Environmental uncertainty strengthens the influence of organizational culture and artificial intelligence-based hotel accounting information systems on internal control systems. Meanwhile, environmental uncertainty does not strengthen the influence of narcissistic behavior on the internal control system. Finally, the internal control system has no effect on fraudulent financial reporting. Keywords: HR Competency; Government Internal Control System (SPIP); Organizational Environment; Financial Reporting Quality and Regional Government Information System (SIPD)